Impacto da associação do uso abusivo de álcool e infecção crônica pelo vírus da hepatite c na apresentação clínica e bioquímica da cirrose hepatica - Farias, Joao Luiz Rodrigues de [UNIFESP] (2018)
Introduction: According to previous data, patients with hepatitis C with alcohol abuse tend to progress more rapidly to cirrhosis and present complications of the disease more often than nonalcoholic patients with HCV infection. Objective: to evaluate the impact of alcohol abuse and chronic hepatitis C virus infection on the clinical and biochemical presentation of liver cirrhosis at the first visit to the outpatient clinic of advanced liver disease at UNIFESP, using as a parameter of comparison patients with cirrhosis of alcoholic or viral etiology exclusively. Methods: Retrospective medical records review. Patients treated for the first time at the outpatient clinic of advanced liver disease of the UNIFESP with diagnosis of liver cirrhosis whose etiology alcohol and / or hepatitis C virus infection age, gender, presence of clinical decompensation (ascites, bleeding gastroesophageal varices, hepatic encephalopathy and jaundice), the presence of comorbidities (systemic arterial hypertension, diabetes mellitus, dyslipidemia, chronic renal disease and hypothyroidism) and biochemical tests (liver enzymes, bilirubin, albumin, prothrombin and creatinine activity) evaluated were. Results: 246 patients with liver cirrhosis of alcoholic etiology (DHA group), 107 with cirrhosis due to chronic hepatitis C virus infection (HCV group) and 58 with concomitant etiologies (group AC) were analyzed. The mean age was around 53 years with no differences between groups. There was a significant predominance of male patients in alcohol abusive groups (87.4% in the DHA group and 75.9% in the AC group versus 48.6% in the HCV group, ² 5,853, p = 0.050). Although the HCV group presented a higher frequency of comorbidities (57.9% vs 41.4% in AC and 45.1% in the HCV group, ² 6.074, p = 0.048), it presented lower number of clinical decompensation prior to the first visit (43% versus about 74% in the other two groups). Patients with alcohol abuse also showed a greater impairment of liver function both by indirect tests (albumin, bilirubin and prothrombin) and by the MELD score (p <0.005). These results with respect to the presentation form and indirect biochemical evaluation of hepatic function were maintained after the exclusion of females in order to homogenise the sample. Conclusion: Patients with cirrhosis due to hepatitis C who were use of alcohol abusive came for the first consultation in a referral clinic for advanced liver diseases with a higher frequency of previous episodes of hepatic decompensation and with a significantly greater functional impairment than those with viral infection alone or ingested only small amounts of alcohol. These results support the hypothesis that alcohol and hepatitis C virus act synergistically for the progression of liver disease.